Identification Of Comparisonal Advantages Of The Agricultural Sector In Lampung Central District - Riky Ardianto; Damara Dinda Nirmalasari Zebua (UNIVED Press, Dehasen University Bengkulu, 2022)
The purpose of this study was to determine the comparative advantage of the agricultural sector in Central Lampung Regency. This study uses secondary data obtained from the Central Statistics Agency (BPS) and other relevant agencies. The analysis technique used is Location Quotient (LQ), Klassen Typology, and Dynamic Location Quotient (DLQ). The LQ results show that the sub-sector, food crops, horticulture, and livestock are the basic sub-sectors, while the plantation and fisheries sub-sectors are non-basic sub-sectors in Central Lampung Regency in 2014-2017. The results of the DLQ show that the plantation sub-sector will be repositioned to become a basic sub-sector in the future. The sub-sectors that did not experience repositioning or shifting were the food crops, horticulture and livestock sub-sectors, where the three sub-sectors became the basic sub-sectors and will remain the basic sub-sectors in the future. The fisheries sub-sector has also not experienced a repositioning where the sub-sector will remain a non-basic sub-sector in the future. The results of Klassen's Typology Analysis show that the horticulture and livestock sub-sector is a developed and rapidly growing sub-sector, the plantation sub-sector is an advanced but depressed sub-sector, the food crops sub-sector is a potential sub-sector, and the fisheries sub-sector is a relatively lagging sub-sector. The sub-sector that has a comparative advantage in Central Lampung Regency is the horticulture and livestock sub-sector because this sub-sector is an advanced and fast-growing sub-sector.